Commercial demand for general takaful - Md. Jadi, Diara (Universiti Utara Malaysia, 2007)
This study is an exploratory study, initially conducted to identify factors that affect retailers demand on General Takaful.This study also aims to evaluate retailers awareness on the existence of the General Takaful and its relationship with educational background and income factors.Level of understanding; relative to the operations and opinions on the scheme is also evaluated.This study employed a convenience sampling method and data were obtained using questionnaires.About 350 questionnaires were distributed and 336 or more than 90% response rate received.The questionnaires were designed to tap into three major part comprising of the demographic background, level of understanding and factors affecting the purchasing of a policy.The findings indicated that almost half of the retailers are aware of the existence of General Takaful and this awareness is significantly related to race and educational level factors.The study also found out that most respondents still have doubts on this scheme which is free from riba.It is noted that even after 22 years in the market, the findings illustrated a low level of understanding of General Takaful and policy ownership among the retailers.